Peran Brand Awareness dalam Meningkatkan Minat Beli Konsumen: Studi Pada Produk Air Minum Dalam Kemasan Merek UNESA - Hidayati, Rika Jannatul; Fahmi, Moh Farih (Jurnal Serambi Ekonomi dan Bisnis, 2024)
In Indonesia, the demand for drinking water continues to increase. Packaged drinking water has become an alternative for people who have difficulty obtaining clean and safe water for consumption. During the last few years, various universities have begun to develop packaged water production as an effort to meet local demands and support environmental programs. One of them is the packaged drinking water product brand "UNESA". The interest of students, especially those who are Muslim, is one of the significant concerns in the context of universities located in countries with a majority Muslim population. This study aims to analyze the effect of halal certification and brand awareness on consumer buying interest in UNESA brand packaged drinking water. Data were analyzed using SEM-PLS technique. The total number of respondents who have filled out the questionnaire is 130 people who are students of Surabaya State University. The data source used in this study comes from primary data. Sampling using non probability sampling technique. The results showed that halal certification and brand awareness have a positive and significant effect on buying interest.